2016
DOI: 10.1136/bmjsem-2015-000053
|View full text |Cite
|
Sign up to set email alerts
|

Video analysis of concussion injury mechanism in under-18 rugby

Abstract: BackgroundUnderstanding the mechanism of injury is necessary for the development of effective injury prevention strategies. Video analysis of injuries provides valuable information on the playing situation and athlete-movement patterns, which can be used to formulate these strategies. Therefore, we conducted a video analysis of the mechanism of concussion injury in junior-level rugby union and compared it with a representative and matched non-injury sample.MethodsInjury reports for 18 concussion events were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 32 publications
4
69
0
Order By: Relevance
“…This study is the first research analyzing tackle situations in which collegiate rugby players experienced a concussion during games. In the previous study, all injured player's previous non-injury situations in the same match and previous matches were extracted as controls 15) . Since the game aspect and tactics change for the opponent team, we considered that it is difficult to compare by simply including tackles extracted from other matches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is the first research analyzing tackle situations in which collegiate rugby players experienced a concussion during games. In the previous study, all injured player's previous non-injury situations in the same match and previous matches were extracted as controls 15) . Since the game aspect and tactics change for the opponent team, we considered that it is difficult to compare by simply including tackles extracted from other matches.…”
Section: Discussionmentioning
confidence: 99%
“…For developing the prevention of concussion, it is essential to clarify inciting events causing concussion. Research on inciting events leading to concussion and HIA with video records has progressed rapidly in recent years [14][15][16][17] . Previous research, targeting the European professional level, suggested there was a higher risk of concussion when the tackler accelerated into a tackle or had head contact with the ball-carrier's head 14,17) .…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in line with the results of previous research on the characteristics of tackles based on video records in rugby union. 7,11,12,19 However, the confidence intervals of these characteristics were fairly wide. It is considered that the numbers within the subgroup, tackles with or without a concussion, were not drastically different in comparison to that for other characteristics, and thus, the standard error was large.…”
Section: Factors Increasing the Likelihood Of The Tackler-related Cmentioning
confidence: 99%
“…In the present study, we defined the control cohort by a different method compared to that used in previous studies on youth and amateur rugby union. 7,11,12 We included the tackles performed by non-concussed tacklers, who played at the same position as that of the concussed tacklers within the same match, as the control cohort. As a result, we identified some new tackling characteristics related to the occurrence of concussion.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…Video analysis studies have provided valuable information on injury Quarrie & Hopkins, 2008) and concussion Hendricks et al, 2015Hendricks et al, , 2016 risk factors in rugby union. This has also been the case for concussion injury research in other sports such as rugby league (Gardner et al, 2015), ice hockey (Hutchison, Comper, Meeuwisse, & Echemendia, 2013) and soccer (Andersen, Arnason, Engebretsen, & Bahr, 2004).…”
Section: Introductionmentioning
confidence: 99%